1982
DOI: 10.1128/iai.37.2.670-678.1982
|View full text |Cite
|
Sign up to set email alerts
|

Protection against pulmonary blastomycosis: correlation with cellular and humoral immunity in mice after subcutaneous nonlethal infection

Abstract: A model of pulmonary blastomycosis in the mouse, in which the portal of entry is the same as natural human infection, was used to study resistance to challenge after subcutaneous infection. One week after subcutaneous infection, mice were partially resistant to pulmonary challenge, and mice challenged two weeks after infection were resistant. Measurement of cellular and humoral immune responses to Blastomyces dermatitidis antigens after subcutaneous infection showed the following. (i) Delayed-type hypersensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…2). These findings are consistent with previous work (22) which showed that peak immunological responses (antigen-induced blastogenesis and delayed hypersensitivity reactions) were optimal 4 weeks postimmunization and then declined. They also suggest that PMN could be activated 24 h after immunized mice were challenged with this pathogen and consequently play a major role in the resistance of mice to reinfection.…”
Section: Wkcsupporting
confidence: 93%
See 3 more Smart Citations
“…2). These findings are consistent with previous work (22) which showed that peak immunological responses (antigen-induced blastogenesis and delayed hypersensitivity reactions) were optimal 4 weeks postimmunization and then declined. They also suggest that PMN could be activated 24 h after immunized mice were challenged with this pathogen and consequently play a major role in the resistance of mice to reinfection.…”
Section: Wkcsupporting
confidence: 93%
“…The conditions necessary for the production of active supernatants by antigen stimulation of sensitized spleen cells correlated with those optimal for proliferative responses reported previously (22), e.g., 4 to 6 days in culture. In contrast, supernatants with macrophage activating factor have been generated by antigen stimulation of sensitized human peripheral blood mononuclear cells (2) or murine spleen cells (4, 10) over shorter culture periods, e.g., 2 or 3 days.…”
Section: Wkcsupporting
confidence: 74%
See 2 more Smart Citations
“…Lung infections with two microorganisms, Mtb and Cryptococcus neoformans (Cne), are discussed in this section as examples of infections requiring intact CMI for resolution. Animal models of chronic lung infections with several other important pathogenic organisms have been studied, including Pneumocystis carinii (Walzer, 1984;Shel-lit0 et al, 1990;Harmsen and Stankiewicz, 1990;Boylan and Current, 1992), Histoplasma capsdatum (Baughman et al, 1986;Defaveri and Graybill, 1991;Fojtasek et al, 1993;Allendoerfer et al, 1993), Blastomyces dermitiditis (Morozumi et al, 1982;Moser et al, 1988;Frey et al, 1989;Williams et al, 1994), Paracoccidiodes braziliensis (Brummer et al, 1984;Defaveri et al, 1989), Coccidiodes immitis (Cox et al, 1988), Chlamydia trachomatis and psittaci (Williams et al, 1988), Rhodococcus equi (Kanaly et al, 1993), and Mycobacterium auiumintracellulare (Takashima and Collins, 1988). Although infection with Legionella pneumophila can cause an acute pneumonia in susceptible hosts, it is a facultative intracellular bacterium; CMI is thought to be necessary for resolution of the infection.…”
Section: B Chronic Bacterial and Fungal Pneumoniasmentioning
confidence: 99%